2020
DOI: 10.1016/j.drudis.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Application of mesoporous silica nanoparticles as drug delivery carriers for chemotherapeutic agents

Abstract: Recently, remarkable efforts have focused on research towards enhancing and delivering efficacious and advanced therapeutic agents. Even though this involves significant challenges, innovative techniques and materials have been explored to overcome these. The advantageous properties of mesoporous silica nanoparticles (MSNs), such as unique morphologies and geometries, makes then favorable for use for various drug delivery targeting purposes, particularly in cancer therapy. As we discuss here, MSNs have been ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 73 publications
0
37
0
Order By: Relevance
“…Therefore, future research should be directed at focusing on how to improve the survival rate of patients with such poor surgical prognoses, including the development of new anti-cancer drugs and molecularly targeted therapies and regimens. The development of potentially more effective anti-cancer agents, carriers for drug delivery, molecularly targeted drugs, and chemotherapy regimens followed by surgical treatment may improve outcomes for patient groups with poor prognoses, even when used in combination with current treatment strategies [29]. Furthermore, it has been reported that nutritional status is associated with the effects and outcomes of chemotherapy [30], and that inflammatory cells in the tumor microenvironment support tumor growth [31]; therefore, the maintenance of nutritional status and perioperative anti-inflammatory strategies may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future research should be directed at focusing on how to improve the survival rate of patients with such poor surgical prognoses, including the development of new anti-cancer drugs and molecularly targeted therapies and regimens. The development of potentially more effective anti-cancer agents, carriers for drug delivery, molecularly targeted drugs, and chemotherapy regimens followed by surgical treatment may improve outcomes for patient groups with poor prognoses, even when used in combination with current treatment strategies [29]. Furthermore, it has been reported that nutritional status is associated with the effects and outcomes of chemotherapy [30], and that inflammatory cells in the tumor microenvironment support tumor growth [31]; therefore, the maintenance of nutritional status and perioperative anti-inflammatory strategies may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor delivery is also enhanced by improved targeting of the tumor microenvironment, leading to the accumulation of the therapeutic molecules in the tumors and thus potentiating the use of combination therapies low biodegradability. Mesoporous inorganic nanoparticles mostly biodegradable, silica-basedconstitute an alternative to protect drugs within a porous structure but their safety profile still needs characterization [11,12]. On the other hand, the organic nanoparticle family exhibits better biocompatibility and biodegradability, making those more suitable for therapeutic applications.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…For instance, in the past decade, mesoporous silica nanoparticles (MSNs) have been exploited as stimuli-responsive nano-carriers for targeted delivery of a wide range of small molecules for diagnostic as well as therapeutic approaches. Major advantages of using MSN-type nano-systems for delivery of cytotoxic cancer drugs are improved drug efficacy, stimuli-responsive controlled release at the target site, and reduced toxic effects to nearby healthy tissues (Alyassin et al, 2020;Aquib et al, 2019;Li, T. et al, 2019;Nguyen et al, 2019). Another area of recent breakthroughs in cancer therapeutics has been in the field of NMs [such as gold nanostructures (Cheng et al, 2014;Lee et al, 2017), carbon dots (Li et al, 2016;Liyanage et al, 2020), carbon nanotubes (You et al, 2019), liposomes (Vieira and Gamarra, 2016;Jena et al, 2020), etc.]…”
Section: Properties Of Nanomaterialsmentioning
confidence: 99%